The Effect of Self-Efficacy and Work Motivation on Elementary School Teachers in Logas Tanah Darat Sub District - Isnan Arif; M.Nur Mustafa; Erlisnawati Erlisnawati (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the influence of self-efficacy and work motivation on the performance of elementary school teachers using the Logas Tanah Darat teaching method. This study used a quantitative approach with an ex post facto method involving 149 teachers, selected proportionally from a population of 236 educators in 17 public elementary schools. Data were collected through questionnaires on self-efficacy, work motivation, and teacher performance. Data analysis was conducted using descriptive statistics, classical assumption tests, and simple and multiple regressions with the help of SPSS 25. The data showed that self-efficacy contributed significantly to teaching performance, reaching 44.7%, indicating that those who are highly confident in their professional skills implement learning more effectively. Work motivation was also a factor, at 47.3%, highlighting how enthusiasm, discipline, and internal commitment shape consistent teaching behavior over time. These two variables, when combined, explained 47.3% of the variation in performance, indicating that psychological self-efficacy and intrinsic motivation are important elements underlying work effectiveness. To improve teaching performance, the study concluded that it is important not only to develop technical skills, but also to strategically invest in strengthening self-efficacy and fostering strong intrinsic motivation to encourage sustainable and high-quality teaching practices.